EFFICACY OF THE METHOD OF SCREENING FOR THROMBOPHILIA IN WOMEN WITH RECURRENT PREGNANCY LOSS - A. I. Mirov; O. N. Kharkevich (IRBIS LLC, 2017)
Thrombophilia is known for its role in the pathogenesis of spontaneous loss of pregnancy. However, in-depth hemostasis tests are costly, and cannot be routinely used. Therefore, the aim of this study was to develop a method adjustable to screening for thrombophilia in women with recurrent pregnancy loss and also to evaluate its efficacy.Materials and methods. A comprehensive examination - clinical, laboratory and instrumental - was performed in 103 women with spontaneous pregnancy loss in the past and 33 women (control) with two or more spontaneous deliveries without significant complications. Diagnosis of thrombophilia was made on the basis of full scale hemostasis tests performed for all patients. The tests included measurements and analyses of 30 standard parameters of hemostasis. Statistical processing of the results was carried out using parametric and nonparametric methods.Results. A thorough assessment of medical history and medical records together with the current results of clinical, instrumental  and laboratory examination allowed us to determine10  major criteria (markers)  for predicting the presence of thrombophilia. These included certain details of medical history, as well as the family and obstetric-gynecological background. The developed markers laid the groundwork for the proposed screening method, where each of the markers gave 1 point to the total score. As part of the screening data analysis, we developed a matrix for the probable risk of having thrombophilia. Selection of patients with a total screening score of 3 or more points allowed increasing 2.6-fold (by 53.4%) the efficacy of laboratory diagnosis of thrombophilia in women with recurrent pregnancy loss.Conclusion. The novelty of the proposed screening method is that the analysis begins at the stage of pregnancy planning and it precedes the laboratory tests; the approach does not require additional expenses. According to our estimate, the use of this method increased the rate of thrombophilia detection by 160%.